(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Suci Indah Nadhifah Sari 04020170408 : This study aims to determine and analyze how Islamic law views divorce due to forced marriage. Also, knowing and analyzing how judges consider divorce due to forced marri age (Decision Study Number 563 / Pdt.G / 2020 / PA.Mks.)This study uses the (Legal Research) method with the type of empirical research, namely research based on field observations. And supported by the addition of Primary Data, namely data or facts obtained directly through field research such as interviews with the Panel of Judges. Meanwhile, secondary data is data that is not directly from the research location but is obtained from several literatures, journals, and laws and regulations.